The influence of föhn winds on annual and seasonal surface melt on the Larsen C Ice Shelf, Antarctica - Turton, Jenny; Kirchgaessner, Amélie; Ross, Andrew N.; King, John C.; Munneke, Peter Kuipers (Cryosphere, 2020)
Warm, dry föhn winds are observed over the Larsen C Ice Shelf year-round and are thought to contribute to the continuing weakening and collapse of ice shelves on the eastern Antarctic Peninsula (AP). We use a surface energy balance (SEB) model, driven by observations from two locations on the Larsen C Ice Shelf and one on the remnants of Larsen B, in combination with output from the Antarctic Mesoscale Prediction System (AMPS), to investigate the year-round impact of föhn winds on the SEB and melt from 2009 to 2012. Föhn winds have an impact on the individual components of the surface energy balance in all seasons and lead to an increase in surface melt in spring, summer and autumn up to 100 km away from the foot of the AP. When föhn winds occur in spring they increase surface melt, extend the melt season and increase the number of melt days within a year. Whilst AMPS is able to simulate the percentage of melt days associated with föhn with high skill, it overestimates the total amount of melting during föhn events and non-föhn events. This study extends previous attempts to quantify the impact of föhn on the Larsen C Ice Shelf by including a 4- year study period and a wider area of interest and provides evidence for föhn-related melting on both the Larsen C and Larsen B ice shelves.
CRIS-Team Scopus Importer:2020-12-11